ANALYSIS OF LEGAL ASPECTS ON SALE AND PURCHASE OF HIGH HERITAGE LAND DISPUTES - Nana Kartika (CERED Indonesia Institute, 2021)
Land disputes are one of the problems that are not easily solved and must be resolved carefully. High inheritance is the common property of a people who have blood ties and are inherited through generations from their earlier ancestors. Buying and selling according to customary law is exchange and is called cash or cash. The problem of ulayat land (high heirloom) can not be traded based on West Sumatra Regulation No. 6 of 2008 concerning ulayat land and its utilization. This study examines what is included in the scope arrangement according to sentence no. 11/Pdt.G/2015/PN. BSK, what factors are the cause of the dispute of high heirloom land and how the settlement of high heirloom land disputes sold is determined by the Batusangkar District Court Data collection techniques using primary data, namely observation and secondary data that is obtained from legislation, books, scientific works related to this research, legal dictionaries, official documents and regulations.